Se l’uomo è ‘persona’ muta il rapporto tra neuroscienze e diritto penale (TEST BioLaw Journal - Rivista di BioDiritto, 2017)
Neuroscience studies the relationship between brain and human behavior, based on different perspectives, whether to deny or not the existence of free will and therefore the criminal responsibility. Also the problem about the function of the punishment is affected by multiple settings, which are now confused in the multifunctional thesis. However, Italian Constitution presents man as a person, holder of inviolable rights, and is fully satisfied only by the essentially rehabilitative finality, for the resocialization of the guilty. Consequently, the dialogue with neuroscience would present the sanctioning response as an appeal to man's decision-making ability, as being-in-relationship.
Keywords: neuroscience; criminal law; function of punishment; man’s conception; Italian Constitution